2010
DOI: 10.1094/phyto-100-4-0313
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Regions Controlling Adult-Plant Stripe Rust Resistance in Chinese Landrace Pingyuan 50 Through Bulked Segregant Analysis

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, is one of the most widespread and destructive wheat diseases worldwide. Growing resistant cultivars with adult-plant resistance (APR) is an effective approach for the control of the disease. In this study, 540 simple sequence repeat markers were screened to map quantitative trait loci (QTL) for APR to stripe rust in a doubled haploid (DH) population of 137 lines derived from the cross Pingyuan 50 x Mingxian 169. The DH lines were planted in randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 24 publications
1
40
1
Order By: Relevance
“…Many APR QTL have been reported on the short arm of chromosome 2B (Boukhatem et al, 2002; Carter et al, 2009; Lan et al, 2010; Lowe et al, 2011; Chen et al, 2012; Mcintosh et al, 2014). Strong associations were detected in the Ethiopian durum wheat panel in the distal part of the short arm of chromosome 2B.…”
Section: Discussionmentioning
confidence: 99%
“…Many APR QTL have been reported on the short arm of chromosome 2B (Boukhatem et al, 2002; Carter et al, 2009; Lan et al, 2010; Lowe et al, 2011; Chen et al, 2012; Mcintosh et al, 2014). Strong associations were detected in the Ethiopian durum wheat panel in the distal part of the short arm of chromosome 2B.…”
Section: Discussionmentioning
confidence: 99%
“…BSA is an efficient and effective method for identifying markers linked to a specific gene or genomic region (27). Although BSA is widely applied in plants, especially for disease resistance (20,27,57), its application to mushrooms is less well known; the identification of markers linked with mushroom weight in A. bisporus (40), mating type factors in L. edodes (18), and the sporeless trait in P. pulmonarius (38) has been reported. This method will be a useful tool for finding markers closely linked to important agronomic traits in mushroom breeding.…”
Section: Discussionmentioning
confidence: 99%
“…The next region also contained a seedling resistance gene derived from Camp Remy (Boukhatem et al 2002), HTAP resistance in Louise (Carter et al 2009) and minor QTLs in Pingyuan50 (Lan et al 2010) and Naxos (Ren et al 2012a). This region was located close to QRYr2B.2 and although the flanking markers from the loci within these two regions did not overlap, limitations in consensus mapping do not rule out the possibility that the same genes may contribute to some resistances in both regions.…”
Section: Groupmentioning
confidence: 99%
“…The QRYr5A.2 chromosomal region (Fig. 5) contained QTLs from four parents, Pastor (Rosewarne et al 2012), Pingyuan 50 (Lan et al 2010), SHA3/CBRD (Ren et al 2012a) and Opata 85 (Boukhatem et al 2002). The first three QTLs were identified in field-based studies and had low to moderate LOD and PEV scores, as well as being inconsistently identified across multiple environments.…”
Section: Groupmentioning
confidence: 99%